ANALISIS KANDUNGAN MINYAK ATSIRI DAUN TENGGULUN (Protium javanicum Burm.F.) DENGAN METODE KROMATOGRAFI GAS-SPEKTROSKOPI MASSA - Sukmajaya A. P. T., I G. P.; Puspawati, N. M.; Bawa Putra, A. A. (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 2 Juli 2012, 2013)
Leaves of Tenggulun are commonly used in traditional medicine for inflammatory therapy. This research aims to analyze the chemical composition of the volatile oil extracted from Tenggulun leaf by gass chromatography (GC) coupled to mass spectrometer (MS). The volatile oil was obtained by steam distillation method. GC-MS spectra demonstrate that the volatile oil of Tenggulun leaf is constituted mainly of monoterpenes such as ?-ocimene (49.87%) and ?-pinene (0.36%) and sesquiterpenes such as ?-caryophyllene (24.95%), germacrene (4.01%), ?-humulene (2.98%), ?-elemene (2.38%), caryophyllene oxide (0.81%), ?-amorphene (0.46%), and spathulenol (2.64%).
Keywords: Tenggulun leaf, steam distillation, volatile oil, GC-MS